2019
DOI: 10.14744/tjtes.2019.21270
|View full text |Cite
|
Sign up to set email alerts
|

Which implant is superior for treating simple pertrochanteric fractures of the proximal femur in the elderly patients?

Abstract: BACKGROUND:The aim of this study was to compare the clinical and radiological results of the proximal femoral nail antirotation (PFNA) with those of the dynamic hip screw (DHS) and percutaneous compression plate (PCCP) in the treatment of simple pertrochanteric fractures. METHODS:A total of 203 patients were included in the study. PFNA fixations were performed in 73 patients (PFNA group), DHS in 68 patients (DHS group), and PCCP in 62 patients (PCCP group). The main outcome measurements were perioperative prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Many implant comparison studies have emphasized that complications are observed less in patients with PFN. [25] Many methods are recommended in the literature to avoid these complications. For example, the use of double scopy during PFN surgery is reported to reduce the surgical duration and complication risks.…”
Section: Discussionmentioning
confidence: 99%
“…Many implant comparison studies have emphasized that complications are observed less in patients with PFN. [25] Many methods are recommended in the literature to avoid these complications. For example, the use of double scopy during PFN surgery is reported to reduce the surgical duration and complication risks.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the time between the injury and surgical treatment is an essential factor for the outcome. The recommendation is to perform surgery up to 48 h after the injury, which reduces the risks of complications and mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%